Magnetic Resonance Imaging Studies on Acupuncture Therapy in Depression: A Systematic Review - Zhang, Jinhuan; Wu, Xiaoxiong; Nie, Dehui; Zhuo, Yuanyuan; Li, Jiaying; Hu, Qingmao; Xu, Jinping; Yu, Haibo (Frontiers in Psychiatry, 2021)
Accumulating studies had been performed using magnetic resonance imaging (MRI) to understand the neural mechanism of acupuncture therapy for depression. However, inconsistencies remain due to differences in research designs and MRI analytical methods. Therefore, we aim to summarize the current MRI research and provide useful information for further research by identifying papers published in English and Chinese about MRI studies on acupuncture for depression up to November 2020. A total of 22 studies met the inclusion criteria, including 810 depression patients and 416 health controls (HC). The applied designs of these studies are mainly random control trial and pre-post designs. The MRI analytical methods are mainly (fraction) amplitude of low-frequency fluctuation (fALFF/ALFF) and functional connectivity (FC), whereas a small subset of studies used voxel-based morphometry (VBM) and diffusion tensor imaging (DTI). The most consistent fMRI results showed increased NAA/Cr ratios, increased AlFF in right precuneus, decreased ALFF in inferior frontal gyrus (IFG) and increased FC of anterior cingulate cortex (ACC). In contrast, no significant neurological changes were identified in any of the DTI or VBM studies. However, clear, reliable conclusions cannot be drawn due to the use of different designs, analytical methods, seed points selected, types of depression, acupuncture points, and so on. Improved report specifications, well-designed studies, consistent analytical methods, and larger sample sizes will enable the field to better elucidate the underlying mechanisms of acupuncture in depressed patients.